Biomarkers to aid in diagnosis of allergic contact dermatitis - Manuel Sargen; Akimi Sasaki; Anish R. Maskey; Xiu-Min Li; Xiu-Min Li; Xiu-Min Li (Frontiers in Allergy, 2025)
Allergic contact dermatitis (ACD) is an increasingly common skin condition characterized by itchy rashes in response to allergens. The most common diagnostic test involves patch testing (PT), but despite the efficacy of PT for identifying and guiding patients toward avoidance of allergens, PT alone does not elucidate the underlying biomechanistic changes which may be useful for sub-categorizing ACD further. In addition, some patients may never be able to identify their causative allergens unless they go to highly specialized ACD centers. Accordingly, this mini review attempts to summarize biomarkers that may help with identifying and sub-categorizing cases of ACD for appropriate diagnosis, especially in patients with difficult-to-identify allergens.